Presurgical cleft lip and palate orthopedics: an overview - Alzain I; Batwa W; Cash A; Murshid ZA (Dove Medical Press, 2017)
Ibtesam Alzain,1 Waeil Batwa,2 Alex Cash,3 Zuhair A Murshid2 1Pediatric Dentistry, 2Orthodontic Department, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 3Cleft Lip and Palate Orthodontics, Queen Victoria NHS Foundation Trust, South Thames Cleft Service, London, UK Abstract: Patients with cleft lip and/or palate go through a lifelong journey of multidisciplinary care, starting from before birth and extending until adulthood. Presurgical orthopedic (PSO) treatment is one of the earliest stages of this care plan. In this paper we provide a review of the PSO treatment. This review should help general and specialist dentists to better understand the cleft patient care path and to be able to answer patient queries more efficiently. The objectives of this paper were to review the basic principles of PSO treatment, the various types of techniques used in this therapy, and the protocol followed, and to critically evaluate the advantages and disadvantages of some of these techniques. In conclusion, we believe that PSO treatment, specifically nasoalveolar molding, does help to approximate the segments of the cleft maxilla and does reduce the intersegment space in readiness for the surgical closure of cleft sites. However, what we remain unable to prove equivocally at this point is whether the reduction in the dimensions of the cleft presurgically and the manipulation of the nasal complex benefit our patients in the long term. Keywords: presurgical orthopedic, nasoalveolar molding, cleft lip and palate